Standard Time Analysis on The Cutting and Packaging Section of Porridge Sticky Rice “JELITA” - Linggar Larasati; Iffan Maflahah; Burhan (Universitas Muhammadiyah Sidoarjo, 2022)
The research aims to determine the standard working time on the cutting and packaging of glutinous jenang